Multi-biofluid metabolomics analysis of allergic respiratory rhinitis and asthma in early childhood - Chih-Yung Chiu, MD, PhD; Meng-Han Chiang, MS; Chieh-Ni Kuo, BS; Mei-Ling Cheng, PhD; Gigin Lin, MD, PhD (World Allergy Organization Journal)
Background: Childhood rhinitis and asthma are allergic respiratory diseases triggered by common allergens, but they affect different parts of the respiratory system, leading to distinct symptoms. However, a comprehensive multi-biofluid metabolomics-based approach to uncover valuable insights into childhood allergies and allergen sensitization remains unaddressed. Methods: Seventy-six children, comprising 26 with rhinitis, 26 with asthma, and 24 healthy controls, were enrolled. Fecal, blood, and urine metabolomic analyses using 1H nuclear magnetic resonance (NMR) spectroscopy were conducted. An integrative analysis of their associations with allergen-specific IgE levels in the context of allergic rhinitis and asthma were also assessed. Results: The analysis of 228 various biofluid samples revealed strong positive correlations between stool and blood metabolites, while blood metabolites exhibited negative correlations with most urine metabolites. Five and 19 metabolites were significantly different in children with rhinitis and asthma, respectively (P < 0.05). Among them, blood isovaleric acid correlated positively with stool IgE levels in rhinitis, while stool butyric acid and acetic acid in asthma exhibited strong negative correlations with total serum and mite allergen-specific IgE levels (P < 0.01). Blood metabolic profiles appeared to have the highest area under the curve (AUC) of 0.732 for rhinitis, whereas stool metabolic profiles had the highest AUC of 0.799 for asthma. Conclusions: Multiple biofluid metabolomics provides comprehensive insights into childhood allergies, with blood profiles associated with allergic rhinitis and fecal profiles linked to asthma. Their short-chain fatty acid metabolites related to IgE levels emphasize the significant role of the gut microbiota in childhood rhinitis and asthma.